2014
DOI: 10.1128/jb.02006-14
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Alters Growth Activity, Autolysis, and Antibiotic Tolerance in a Human Host-Adapted Pseudomonas aeruginosa Lineage

Abstract: Interactions among members of polymicrobial infections or between pathogens and the commensal flora may determine disease outcomes. Pseudomonas aeruginosa and Staphylococcus aureus are important opportunistic human pathogens and are both part of the polymicrobial infection communities in human hosts. In this study, we analyzed the in vitro interaction between S. aureus and a collection of P. aeruginosa isolates representing different evolutionary steps of a dominant lineage, DK2, that have evolved through deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 37 publications
5
101
0
Order By: Relevance
“…For example, S. maltophilia has been observed to influence P. aeruginosa biofilm architecture and protein synthesis (Ryan et al. 2008), while P. aeruginosa has been shown to have negative effects on S. aureus due to upregulation of antistaphylococcal substances such as pyocyanin and phenazine (Michelsen et al., 2014). Even though S. aureus has not been shown to have direct negative effects on P. aeruginosa , the S. aureus presence has been shown to favour the increase in the frequency of QS‐deficient mutants (Harrison et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, S. maltophilia has been observed to influence P. aeruginosa biofilm architecture and protein synthesis (Ryan et al. 2008), while P. aeruginosa has been shown to have negative effects on S. aureus due to upregulation of antistaphylococcal substances such as pyocyanin and phenazine (Michelsen et al., 2014). Even though S. aureus has not been shown to have direct negative effects on P. aeruginosa , the S. aureus presence has been shown to favour the increase in the frequency of QS‐deficient mutants (Harrison et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Even though S. aureus has not been shown to have direct negative effects on P. aeruginosa , the S. aureus presence has been shown to favour the increase in the frequency of QS‐deficient mutants (Harrison et al., 2008). In line with this study, it has been found that a QS‐positive PAO1 strain interacts more negatively with S. aureus compared to a QS‐negative lasR strain (Michelsen et al., 2014). Recent evidence suggests that reduced antagonism between S. aureus on P. aeruginosa lasR mutants could be due to metabolic divergence (Frydenlund Michelsen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This report additionally found that agtR, a response regulator involved in metabolite sensing and uptake, was required for this activity, suggesting metabolite sensing as a possible means for bacterial cross talk. An additional report indicated that S. aureus secretes one or more proteins to manipulate the growth characteristics of P. aeruginosa (53). It is therefore likely that iron-regulated AQ production is not the sole driver of interactions between these two bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture with S. aureus similarly promotes selection of P. aeruginosa SCVs, resulting in increased survival and antimicrobial tolerance of P. aeruginosa isolates in the CF lung (Michelsen et al 2014). This interaction is dependent upon the Agr quorum sensing system, which regulates the expression of multiple virulence factors in S. aureus (Novick 2003).…”
Section: Commensal and Mutualistic Interactionsmentioning
confidence: 99%
“…Analysis of the DK-2 lineage of P. aeruginosa , isolated from multiple CF patients between 1973 and 2008 (Yang et al 2011), showed that this strain's ability to inhibit S. aureus growth was reduced as it adapted to the CF lung environment (Michelsen et al 2014). A separate analysis of 24 P. aeruginosa isolates from 8 distinct CF patients at multiple stages of chronic lung infection showed a similar reduction in the ability of P. aeruginosa to inhibit S. aureus growth (Baldan et al 2014).…”
Section: Parasitic Interactionsmentioning
confidence: 99%